Online flipped classroom in university social science courses: Impact on student experience and success - Mitja Dečman; Maja Klun; Janez Stare (Computers and Education Open)
The flipped classroom model has recently gained recognition for promoting personalised learning, supporting student-centred and peer-supported instruction, and optimising class time for active learning of higher order thinking skills. However, it requires students to work independently and in isolation, which is particularly challenging in a fully online implementation and in non-STEM courses where group work, discussion and other forms of active learning are essential.The research focused on two flipped online social science courses and involved quantitative analysis of data collected before and after the courses. The surveys examined the perceived and experienced drivers and barriers associated with flipped courses, including the use of video lectures, self-directed learning, self-discipline, social isolation, motivation, and time management. In addition, the study examined the impact of group activities on exam grades, such as discussion, presentations and interpretative assignments relevant to non-STEM courses. Another focus was on the impact of previous experiences with blended learning and online learning.The results showed that although students were not initially familiar with the flipped classroom model, they appreciated the flexibility of learning at their own pace and being able to re-watch video lectures. Despite their concerns about social isolation, students did not express any significant anxiety in this regard. The study also found statistically significant differences between students with blended learning and online learning experiences. The most significant predictor of a good exam grade was weekly participation in an online forum, followed by weekly collaborative group activities such as discussion, presentations and interpretations, which are essential for non-STEM students.